The Basis Of Civil Liability For Oil Pollution In Iraqi Law - Kadhim Jawad, Ali (Opción, 2019)
Environmental damage is considered to be of a special nature, and therefore the general rules contained in the Iraqi Civil Law No. 40 of 1951 may not be sufficient to determine the value of compensation for damage resulting from environmental pollution. The legislator has not explicitly addressed the legal basis for environmental damage, but can resort to the rules The public con- tained therein to determine the basis for this responsibility in addition to what is stated in the Law for the Protection and Improvement of the Environment No. (27) for the year 2009, which is based on the existence of a fault and dam- age and a causal relationship between them, whether the cause of the damage is a natural or legal person with the possibility of amending the laws in force to determine the basis of civil liability Contamination E oil SAVING damaged rights, as well as in general environmental protection.